2022
DOI: 10.1039/d2ra01570f
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the potential of pesticide-tolerant Pseudomonas sp. augmenting biological and physiological attributes of Vigna radiata (L.) under pesticide stress

Abstract: In the agricultural domain, chemical pesticides are repetitively and harshly used to kill harmful pests, but they often pose a serious threat to microbial diversity, soil fertility and agricultural output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 77 publications
0
3
1
Order By: Relevance
“…However, at a higher 3,000 μg/ml (T-4) CBZM concentration, there was no P-solubilizing activity observed. The results are in contrast with other findings of earlier research where Pseudomonas fluorescens showed a declining trend of TCP solubilization under pesticide treatment ( Al-Enazi et al, 2022 ).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…However, at a higher 3,000 μg/ml (T-4) CBZM concentration, there was no P-solubilizing activity observed. The results are in contrast with other findings of earlier research where Pseudomonas fluorescens showed a declining trend of TCP solubilization under pesticide treatment ( Al-Enazi et al, 2022 ).…”
Section: Resultscontrasting
confidence: 99%
“…Results showed that the amount of ACCD was reduced by 38.9, 64.1, and a maximum of 92.3 at 1,000 μg/ml (T-2), 2,000 μg/ml (T-3), and 3,000 μg/ml (T-4) fungicide levels, respectively, over unstressed control (T-1). Several studies ( Syed et al, 2021 ; Al-Enazi et al, 2022 ) have found that fungicides and heavy metals reduce the ACC deaminase activity of soil bacteria in a similar way.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Incorporating both isolates can be a practical approach for remediating fungicide-contaminated soil, as well as enhancing radish plant growth while reducing fungicide inputs. Enhazi [66] conducted a study to assess the efficacy of plant growth-promoting (PGP) rhizobacterial strains that are resistant to pesticide toxicity. The researchers isolated Pseudomonas sp.…”
Section: Phytohormone Production For Reducing Fungicides and Pesticidesmentioning
confidence: 99%